Critical pleasures reflections on the Indonesian horror genre and its anti-fans - Downes, Meghan (Plaridel, 2015)
Access online through this link: https://www.plarideljournal.org/article/critical-pleasures-reflections-on-the-indonesian-horror-genre-and-its-anti-fans